European Respiratory Society International Congress 2018: four shades of epidemiology and tobacco control - (:unkn) unknown (EUROPEAN RESPIRATORY SOC JOURNALS LTD, 2019)
In this article, early career members and experienced members of the Epidemiology and Environment Assembly of the European Respiratory Society highlight and summarise a selection of six sessions from the Society's annual congress, which in 2018 was held in Paris, France. The topics covered in these sessions span from cutting-edge molecular epidemiology of lung function to clinical, occupational and environmental epidemiology of respiratory disease, and from emergent tobacco products to tobacco control.
Keywords: GENOME-WIDE ASSOCIATION; LUNG-FUNCTION; DISEASE; HEALTH; COPD